Acute Esophageal Necrosis in a Septic Patient with a History of Cardiovascular Disease - Michael Coles; Victoria Madray; Pearl Uy (Case Reports in Gastrointestinal Medicine)
Acute esophageal necrosis (AEN), or colloquially named “black esophagus,” is a rare clinical condition often associated with ischemic injury to the esophagus secondary to splanchnic vasoconstriction during hypotensive episodes. We present a case of a 78-year-old man with extensive cardiovascular disease who was initially admitted for gallstone pancreatitis and possible cholangitis. His hospital course was complicated by possible sepsis secondary to aspiration pneumonia and hematemesis secondary to acute ischemic esophageal necrosis as noted on upper endoscopy. Interestingly, the patient only had a transient episode of hypotension (approximately 35 minutes) not requiring vasopressor support, which improved with fluid resuscitation, and endoscopic retrograde cholangiopancreatography (ERCP) done 3 days prior showed normal esophageal mucosa. Clinicians should be aware of the possibility of acute esophageal necrosis as a potential etiology of gastrointestinal (GI) bleed in patients with cardiovascular disease and sepsis.